Changes in the pattern of brachiopod biogeography in northern Asia through early and middle Devonian times - Talent, John A.; Yolkin, Yevgeniy A.; Yolkina, Valentina N.; Kipriyanova, Tat'yana P.; Gratsianova, Rimma T. (Springer, Springer Nature, 2012)
Changes in the biogeographic pattern obtained by mathematical investigation of the brachiopod database from five of the seven Devonian stages, Lochkovian–Givetian, are presented as evidence for substantial relative movements of several of the crustal blocks during Devonian times in what now constitutes northern Asia. Such movements—identified by the end results of evolution and extinction in isolation—would, surely, have substantially pre-dated development of the biogeographic contrasts revealed by mathematical analysis. How much time would have been required to develop such contrast remains problematic. Strong biotic linkage existed between the eastern and western flanks of the Urals through the Lochkovian and Pragian with significant linkage to the Salair and Altai. Linkage between faunas from the two flanks of the Urals weakened for the early and late Emsian but was re-established for the Eifelian and early Givetian; this may be interpreted as perhaps connected with a prior interlude of substantial (though not overwhelmingly wide) separation of the East and West Urals terranes along the Urals Suture. Biotic linkage of the Urals terranes with the Salair and Altai weakened in the Emsian, increased in the Eifelian, then declined and, curiously, contrasting with what happened over most of the globe, disappeared in the Givetian—consistent with major separation of the crustal blocks in question. Strong linkage between the Taymyr and Settedaban regions and significant linkage between them and the Salair and Altai were maintained through the Lochkovian and Pragian. Faunal interaction with the Salair and Altai became inconsequential from the Pragian onwards; this is interpreted as possibly reflecting substantial separation of these terranes from the old Siberian continent, or as a reflection of increased marine-biogeographic differentiation around the old continental margin. Weakening of linkage through the Lochkovian and Pragian for the Novaya Zemlya region accords with increasing and, finally, near-total biologic ...